Plasma lipid peroxide levels and antioxidant enzyme activities in type II diabetics: Relationship with diabetic microangiopatic complications - Akgul, E; Ilhan, N; Halifeoglu, I; Var, A (Elsevier Sci Ireland Ltd, 1997)
[Abstract Not Available]